Diagnosis of an Umbilical Vein Aneurysm at 30 Weeks Gestation. (16th November 2021) - Campbell, Meredith S.; Craig, Amanda M.; Reese, Jeff; Crum, Alicia K.; Patel, Soha S.
Abstract : Background . Fetal umbilical vein aneurysm is an uncommon anomaly without clear guidelines regarding the management of these pregnancies. Case Presentation . We describe an ultrasound diagnosis of this condition involving a 38-year-old multigravid woman who presented at 30 weeks and 3 days gestation with severe fetal growth restriction, reverse end-diastolic flow on umbilical artery dopplers, elevated ductus venosus doppler, and an umbilical vein aneurysm. Due to nonreassuring fetal assessment in the setting of an umbilical vein aneurysm, she underwent a cesarean delivery with a favorable neonatal outcome. Conclusions . There are currently no guidelines for the management of an umbilical vein aneurysm. This case demonstrates a successful multidisciplinary approach for creating a plan of care focused on achieving a favorable outcome for a fetus with a large umbilical vein aneurysm. The approach took into account timing of delivery given the potential for fetal morbidity and mortality, while factoring in the risk of prematurity.